2019
DOI: 10.1038/s41389-019-0122-6
|View full text |Cite|
|
Sign up to set email alerts
|

Dihydroartemisinin inhibits prostate cancer via JARID2/miR-7/miR-34a-dependent downregulation of Axl

Abstract: Axl expression is deregulated in several cancer types, predicts poor overall patient survival and is linked to resistance to drug therapy. Here, we evaluated a library of natural compounds for inhibitors of Axl and identified dihydroartemisinin, the active principle of the anti-malarial drug artemisinin, as an Axl-inhibitor in prostate cancer. Dihydroartemisinin blocks Axl expression leading to apoptosis, decrease in cell proliferation, migration, and tumor development of prostate cancer cells. Dihydroartemisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 68 publications
(94 reference statements)
1
44
0
Order By: Relevance
“…DHA and artesunate are the most studied ART derivatives for cancer treatment, and artesunate will be discussed in a separate section. The anti-cancer effects of ARTs are demonstrated in a broad spectrum of cancer cells including lung, liver, pancreatic, colorectal, esophageal, breast, ovarian, cervical, head and neck, and prostate cancers [183][184][185][186][187][188][189][190][191]. The anti-cancer activities of ARTs include induction of apoptosis and cell cycle arrest, inhibition of cell proliferation and growth, metastasis and angiogenesis [189,[192][193][194][195].…”
Section: Artemisininsmentioning
confidence: 99%
“…DHA and artesunate are the most studied ART derivatives for cancer treatment, and artesunate will be discussed in a separate section. The anti-cancer effects of ARTs are demonstrated in a broad spectrum of cancer cells including lung, liver, pancreatic, colorectal, esophageal, breast, ovarian, cervical, head and neck, and prostate cancers [183][184][185][186][187][188][189][190][191]. The anti-cancer activities of ARTs include induction of apoptosis and cell cycle arrest, inhibition of cell proliferation and growth, metastasis and angiogenesis [189,[192][193][194][195].…”
Section: Artemisininsmentioning
confidence: 99%
“…Dihydroartemisinin (DHA), an antimalarial drug derivative from artemisinin, was reported own powerful anticancer effect on numerous kinds of cancers in vitro and in vivo, such as prostate cancer [8], ovarian cancer [9,10], cervical cancer [11], gallbladder cancer [12] and gastric cancer [13]. In esophageal cancer, Jiang and coauthors [14] reported that DHA performed a powerful anticancer effect toward EC cell lines Eca109 and Ec9706 in vitro and in vivo.…”
mentioning
confidence: 99%
“…Soluble Axl binds to Gas6 or Axl itself, thereby inhibiting the transmembrane Axl and Gas6 signaling pathway [93]. Besides, it has been shown that natural compounds such as celastrol [94] and dihydroartemisinin [95] show therapeutic potential through Axl inhibition.…”
Section: Tam Targetingmentioning
confidence: 99%